Educating children with learning disabilities : selected readings - Frierson, Edward C. ;Barbe, Walter B. (New York : Appleton-Century-Crofts, 1967)
The Essential concern of this book is the child who needs special education for consideration as mentally retarded, emotionally disturbed, visually handicapped, or severely speech- and hearing-impaired. The selections provide a systematic introduction and guide to a more intensive study of special learning disabilities in children. Often the child with special learning disabilities has learning needs and problems similar to those of children classified in other categories, but just as often he has problems, unique to his special deficit, which may be a perceptual, neurological, biochemical, or other specific disorder. The organization of this book should appeal to the general educator as well as to the clinical specialist or college instructor. Sections are arranged for sequential study, yet the presentation of each group of articles allows them to be considered individually.
I. Introduction to learning disorders -- II. Specialized approaches to learning disorders -- III. Diagnosing learning disorders -- IV. Teaching the child with learning disorders.
Includes bibliographical references and index.
Keywords: SPECIAL EDUCATION